THE IMPACT OF PIPE DEALS ON INDIAN COMPANIES - Saraf, Rahul (2008)
This dissertation is an empirical study of the impact of PIPE deals on Indian companies. The private equity market in India especially PIPE has witnessed a very rapid growth in the recent past. As many Indian public companies are increasingly adopting the private route for funds mobilization and thereby choosing to make private offering only to sophisticated and qualified investors rather than issuing it publicly. This can be seen from the fact that in the year 2007 itself, around 387 companies raised $14,234 million through private placements. This empirical study is an attempt based on the event study methodology. The data set comprises of 15 companies, which issued 'private equity' in the year 2007. The report suggest that there are positive announcement effect associated to a PIPE deal which fades out after the initial period and the impact becomes negative in the long run.